Science in Engineering Curriculum a Comparative Study - Brake, A. B. (Journal of Engineering Education Transformations, 2000)
Considering the importance of basic science in engineering curriculum and looking at the attitude of so called technologist against basic science, this paper is aimed at the comparison of engineering curriculum adopted in India with that adopted in developed countries.